Vaccination with immune complexes modulates the elicitation of functional antibodies against HIV-1 - Hioe, Catarina E.; Liu, Xiaomei; Banin, Andrew N.; Heindel, Daniel W.; Klingler, Jéromine; Rao, Priyanka G.; Luo, Christina C.; Jiang, Xunqing; Pandey, Shilpi; Ordonez, Tracy; Barnette, Philip; Totrov, Maxim; et al. (Frontiers in Immunology, 2023)
Introduction Neutralizing antibodies (Abs) are one of the immune components required to protect against viral infections. However, developing vaccines capable of eliciting neutralizing Abs effective against a broad array of HIV-1 isolates has been an arduous challenge. Objective This study sought to test vaccines aimed to induce Abs against neutralizing epitopes at the V1V2 apex of HIV-1 envelope (Env). Methods Four groups of rabbits received a DNA vaccine expressing the V1V2 domain of the CRF01_AE A244 strain on a trimeric 2J9C scaffold (V1V2-2J9C) along with a protein vaccine consisting of an uncleaved prefusion-optimized A244 Env trimer with V3 truncation (UFO-BG.ΔV3) or a V1V2-2J9C protein and their respective immune complexes (ICs). These IC vaccines were made using 2158, a V1V2-specific monoclonal Ab (mAb), which binds the V2i epitope in the underbelly region of V1V2 while allosterically promoting the binding of broadly neutralizing mAb PG9 to its V2 apex epitope in vitro. Results Rabbit groups immunized with the DNA vaccine and uncomplexed or complexed UFO-BG.ΔV3 proteins (DNA/UFO-UC or IC) displayed similar profiles of Env- and V1V2-binding Abs but differed from the rabbits receiving the DNA vaccine and uncomplexed or complexed V1V2-2J9C proteins (DNA/V1V2-UC or IC), which generated more cross-reactive V1V2 Abs without detectable binding to gp120 or gp140 Env. Notably, the DNA/UFO-UC vaccine elicited neutralizing Abs against some heterologous tier 1 and tier 2 viruses from different clades, albeit at low titers and only in a fraction of animals, whereas the DNA/V1V2-UC or IC vaccines did not. In comparison with the DNA/UFO-UC group, the DNA/UFO-IC group showed a trend of higher neutralization against TH023.6 and a greater potency of V1V2-specific Ab-dependent cellular phagocytosis (ADCP) but failed to neutralize heterologous viruses. Conclusion These data demonstrate the capacity of V1V2-2J9C-encoding DNA vaccine in combination with UFO-BG.ΔV3, but not V1V2-2J9C, protein vaccines, to elicit homologous and heterologous neutralizing activities in rabbits. The elicitation of neutralizing and ADCP activities was modulated by delivery of UFO-BG.ΔV3 complexed with V2i mAb 2158.